AI and innovation in HRM : the future of strategic HR in the service economy - Dutta, Pushan, 1985-; Padhi, Amarnath; Das, Sulagna; Sharma, Vinod Kr; Yu, Poshan (Routledge studies in innovation, organizations and technology, 2026)
This book provides a comprehensive blueprint for organizations to strategically leverage AI technologies and drive innovation in their HRM practices, enabling them to cultivate a future-ready workforce that can thrive in the service-centric marketplace. It weighs in on the challenges and opportunities brought forth by the convergence of AI and HRM in a rapidly evolving service economy.Drawing insights from management theory, organizational psychology, and technology studies, this multidisciplinary book explores how AI can augment and elevate various facets of strategic HRM, from talent acquisition and employee development to performance management and organizational culture enhancement. It offers a future-focused perspective on HRM's evolving role in shaping the workplace of tomorrow, emphasizing the pivotal role of AI in fostering organizational agility, innovation, and competitiveness. The international contributors delve into the unique challenges and opportunities presented by AI integration in service industry contexts, providing tailored strategies and best practices for effective adoption, as well as addressing ethical considerations and responsible governance of AI systems.This timely volume will be a valuable resource for scholars across human resource management, organizational management, and innovation and technology management. It will be useful to HR professionals, business leaders, and decision-makers in service-based organizations.